Methodical instructions for possessing Lecture Material and fulfillment of Individual Work in the course “Finance of Enterprises” (compulsory component of Educational Program 075 “Marketing”) for students of the specialty 075 "Marketing" educational degree "Bachelor" - Alekseieva, Kateryna A. (NULES of Ukraine, 2023)
The purpose of teaching the discipline “Finance of Enterprises” is to provide students with fundamental theoretical and practical knowledge about the organization of financial activities of enterprises, the peculiarities of the formation of financial resources, mastering methods of assessing the financial condition of enterprises and financial planning. The objectives of studying the discipline “Finance of Enterprises” are to study the essence and functions of enterprise finance, financial resources and sources of their formation; organization of enterprise finances; acquisition of financial calculation skills; mastering the methods of financial planning; assessment of financial condition, rehabilitation of enterprises.
Recommended by the Academic Council of the Faculty of Agrarian Management of the NULES of Ukraine.
Keywords: Finance of Enterprises; Marketing; фінанси підприємства; маркетинг